Polymorphisms in the putative micro-RNA-binding sites of mesothelin gene are associated with serum levels of mesothelin-related protein. Issue 4 (26th October 2009) - Cristaudo, Alfonso; Foddis, Rudy; Bonotti, Alessandra; Simonini, Silvia; Vivaldi, Agnese; Guglielmi, Giovanni; Bruno, Rossella; Landi, Debora; Gemignani, Federica; Landi, Stefano
Abstract : Background: Serum mesothelin, also known as soluble mesothelin-related protein (SMRP), reportedly shows increased levels in epithelial-type malignant pleural mesothelioma, but sometimes also arrives at high values in healthy asbestos-exposed subjects. Objectives: This study aimed to investigate whether single nucleotide polymorphisms in the 3′untranslated region (3′UTR) of the mesothelin-encoded gene ( MSLN ) are associated with the SMRP levels measured in serum. Methods: The 3′UTR of the mesothelin gene was genotyped in 59 healthy asbestos-exposed subjects, selected on the basis of their SMRP levels. Direct sequencing did not show any new polymorphism, but enabled us to genotype two known SNPs (rs1057147, rs57272256). Differences in the mean values of SMRP in wild-type and variant heterozygote groups were calculated. Results: High levels of SMRP in healthy asbestos-exposed subjects were significantly associated with polymorphism rs1057147 (G<A). Regarding rs57272256, there was no statistically significant difference between wild-type and heterozygote groups. Our study suggests that rs1057147 polymorphism can affect mesothelin expression. Although these data need to be confirmed with a larger number of cases, this study warrants further research in order to better understand the relationship between mesothelin polymorphisms and SMRP.